Diversity, ecology, and distribution of non-indigenous freshwater fish in Malaysia. - Abdul Rahim, Khairul Adha (2012)
Introduction of non-indigenous species have resulted in major global change, harming indigenous species and communities throughout the world and also have caused enormous economic damage. Thus, the main objectives of this study were to examine the composition, ecology, and distribution of non-indigenous fish species in natural water bodies and also evaluate the role and contribution of non-indigenous fish species through aquaculture or stock enhancement in socio-economic development in Malaysia. The studies were carried out at five locations in Peninsular Malaysia and six locations in Sabah and Sarawak. The habitats surveyed in Malaysia include rivers and streams in highland and lowland areas, floodplain and large river system, rice fields, irrigation canal, ex-mining lakes, national park, and estuaries. A total of 4055 individual fish representing 150 species belonging to 38 families were captured. This included 67 species and 24 families from Peninsular Malaysia, and 113 species from 30 families of indigenous fish as well as non-indigenous from Sabah and Sarawak. Out of 150 fish species, 17 species from eight families were identified as non-indigenous. The family Cichlidae represented the highest species collection (5 species) followed by Cyprinidae (4 species), two species from families of Clariidae and Pangasiidae, and one species from families of Charachidae, Helostomatidae, Belontiidae and Loricariidae respectively. The present study has shown that non-indigenous fish occurred and inhabited diverse habitats including highland and isolated streams, rivers, rice fields, swamps, drainage, dam and reservoirs, ex-mining lakes and estuaries in Malaysia. The intentional and unintentional introduction of non-indigenous fish species for various purposes, such as aquaculture development, aquarium fish industry, recreational fishing activities, natural disasters, biological control, and continuous released by Buddhist followers as part of their religious activities have caused a widespread distribution and establishment of nonindigenous species in local ecosystems. In addition, the occurrence of non-indigenous species, not only changed the structure of indigenous ichthyofauna group but also caused ecological and economical damages to local fishermen. The present finding provided evidence that there are no restrictions or limitation of spreading of non-indigenous fish in natural habitats of Malaysia. In the present study, a total of 42 non-indigenous species were recorded. Based on the records and field surveys, the number of introduced fish species was increased almost double than the previous records. Most of the species introduced mainly for aquaculture development and only a few introduced fish species for recreational fisheries, biological control and aquarium fish industries. The aquaculture industry has also encouraged introduction of ‘aquaculture species’ and has become the major reason for introducing non-indigenous fish species into Malaysia. The non-indigenous fishes that have been introduced for food fisheries and aquaculture development include Chinese carps (Hypophthalmichthys nobilis, Cirrhina molitorella, Ctenopharyngodon idella, Cyprinus carpio, Hypophthalmichthys molitrix,); Indian carps (Catla catla, Cirrhina mrigala, Labeo rohita); Javanese carp (Barbonymus gonionotus); African catfish (Clarias gariepinus) and broadhead catfish (Clarias macrocephalus); snakeskin gouramy (Trichogaster pectoralis) and red promfet (Colossoma sp). The tilapias (Oreochromis spp.) together with their hybrids such as Mozambique tilapia (Oreochromis mossambicus), Nile tilapia (O.niloticus, O. urolepis hornorum), hybrid tilapia (O. hornorum and O. mossambicus, red tilapia hybrid) and redbelly tilapia (Tilapia zillii) are also the important species in aquaculture development in Malaysia. This study has recorded a potential new species, Scortum barcoo, for aquaculture development in Malaysia. It showed that the rate and number of non-indigenous fishes introduced in local habitat has greatly increased since the early twentieth century.